Strategi Membangun Citra Lembaga Pendidikan Islam yang Efektif: Konsep Dasar Manajemen Humas Berbasis Al-Qur'an - Salsabila Qurratu'ain 'Abidah -; Rustam Ibrahim (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Building a positive image of Islamic educational institutions is a strategic challenge in the era of global and digital competition. Public relations management based on the values of the Qur'an is the key to the effectiveness of image-building and a differentiator from conventional institutions. This article aims to examine effective strategies for building the image of Islamic educational institutions through the basic concepts of public relations management from an Islamic perspective. The method used is library research with descriptive-qualitative analysis of relevant literature, journals, and documents. The results show that effective strategies include the integration of divine values such as honesty (ṣidq), trustworthiness (amānah), good communication (qaulan sadīda), deliberation (syūrā), and information clarification (tabayyun) into every stage of public relations management (planning, organizing, actuating, controlling). The application of this strategy has been proven to increase public trust, reputation, and institutional sustainability. This article recommends strengthening Islamic-based public relations capacity and further empirical research